Nox2 NADPH oxidase has a critical role in insulin resistance-related endothelial cell dysfunction. - Sukumar, P; Viswambharan, H; Imrie, H; Cubbon, R; Yuldasheva, N; Gage, M; Galloway, S; Skromna, A; Kandavelu, P; Santos, C; Gatenby, V; Smith, J; et al. (2013)
Insulin resistance is characterized by excessive endothelial cell generation of potentially cytotoxic concentrations of reactive oxygen species. We examined the role of NADPH oxidase (Nox) and specifically Nox2 isoform in superoxide generation in two complementary in vivo models of human insulin resistance (endothelial specific and whole body). Using three complementary methods to measure superoxide, we demonstrated higher levels of superoxide in insulin-resistant endothelial cells, which could be pharmacologically inhibited both acutely and chronically, using the Nox inhibitor gp91ds-tat. Similarly, insulin resistance-induced impairment of endothelial-mediated vasorelaxation could also be reversed using gp91ds-tat. siRNA-mediated knockdown of Nox2, which was specifically elevated in insulin-resistant endothelial cells, significantly reduced superoxide levels. Double transgenic mice with endothelial-specific insulin resistance and deletion of Nox2 showed reduced superoxide production and improved vascular function. This study identifies Nox2 as the central molecule in insulin resistance-mediated oxidative stress and vascular dysfunction. It also establishes pharmacological inhibition of Nox2 as a novel therapeutic target in insulin resistance-related vascular disease.